Improved Performance of GaAs-Based Terahertz Emitters via Surface Passivation and Silicon Nitride Encapsulation - Headley, C; Fu, L; Parkinson, P; Xu, X; Lloyd-Hughes, J; Jagadish, C; Johnston, M (2011)
We have improved the stability and performance of terahertz (THz) photoconductive (Auston) switches using a combination of (NH4) 2S surface passivation (SP) and silicon nitride (Si3 N4) encapsulation. The influences of SP and encapsulation on the ultrafast electron dynamics in GaAs were examined using THz emission spectroscopy and optical pumpTHz probe spectroscopy. The power of THz radiation from the surface of photoexcited GaAs increased by a factor of 5 after passivation and encapsulation, while the process lengthened the trapping time for photoexcited charge carriers. By fabricating and assessing the performance of photoconductive switches, we found that passivation and encapsulation increased the average THz power generated fourfold. © 2010 IEEE.